A Fit between Logistics and Supply Chain Management Education and Jobs Market Need in Nepal - JBR, Subarna Bir; Yadav, Umesh Singh (Journal of Nepalese Business Studies, 2021)
The purpose of this paper is to explore a fit between Logistics and Supply Chain Management (LSCM) related course content and the industry needs in the Nepalese context. Since this study is undertaken using the Nepalese sample, the knowledge and skills prioritized by employers, it can be of value to educators while designing their LSCM course content. Desk-based research involving content analyses was done to understand the supply side information i.e. relative coverage of LSCM topics in business-related courses and degrees offered at selected five Nepalese Universities and for the demand side information i.e. analysis of job description of the LSCM related vacancies in the Nepalese job market over eighteen weeks. The study reveals that the inclusion of LSCM courses in the business programs at Nepalese Universities is currently negligible as none of them offered a separate program dedicated to LSCM. Besides, the LSCM courses were limited to just one course per program weighing not more than three credit hours. Instead, there seems to be an unprecedented number of business schools and colleges leaning towards more sellable traditional business degrees related to finance, marketing, human resource management, IT, and hospitality. Finally, when comparing the relative coverage of LSCM topics in the curriculum to the relative demand for such knowledge by the employers, there seems to be an over-emphasis or under-emphasis of courses related to LSCM both at the bachelors and masters level indicating a mismatch between the expectations of employers and education offered by the universities.